Online Hemoglobin and Oxygen Saturation Sensing During Continuous Renal Replacement Therapy with Regional Citrate Anticoagulation. Issue 5 (September 2015) - Yessayan, Lenar T.; Yee, Jerry; Frinak, Stan; Szamosfalvi, Balazs
Abstract : Optical hemoglobin and oxygen saturation sensor (OHOS) monitor when used in combination with other hemodynamic tools may be useful for continuous hemodynamic monitoring during ultrafiltration. The stand-alone OHOS monitor can easily be deployed predialyzer into the extracorporeal circuit of continuous renal replacement therapy (CRRT) systems. To maximize the accuracy of the OHOS in 24 hr CRRT systems, clotting in the optical blood chamber and the presensor dilution incurred by replacement fluid should be minimized. Sustained low-efficiency dialysis (SLED) with regional citrate anticoagulation is a therapy that incorporates an OHOS and maintains the overall reliability of hemoglobin (Hb) and saturation sensing. The system operates at a blood flow rate of 60 ml/min and a fixed acid citrate infusion rate of 150 ml/hr. The presensor dilution incurred by concentrated citrate infusion would result in a minimal Hb dilution (<0.7 g/dl) while minimizing optical blood chamber clotting during 24 hr SLED.